Serum response factor (SRF) ablation interferes with acute stress-associated immediate and long-term coping mechanisms - Zimprich, Annemarie; Bekeredjian, Raffi (Molecular neurobiology, 2017)
Stress experience modulates behavior, metabolism, and energy expenditure of organisms. One molecular hallmark of an acute stress response is a rapid induction of immediate early genes (IEGs) such as c-Fos and Egr family members. IEG transcription in neurons is mediated by the neuronal activity-driven gene regulator serum response factor (SRF). We show a first role of SRF in immediate and long-lasting acute restraint stress (AS) responses. For this, we employed a standardized mouse phenotyping protocol at the German Mouse Clinic (GMC) including behavioral, metabolic, and cardiologic tests as well as gene expression profiling to analyze the consequences of forebrain-specific SRF deletion in mice exposed to AS. Adult mice with an SRF deletion in glutamatergic neurons (Srf; CaMKIIa-CreERT2 ) showed hyperactivity, decreased anxiety, and impaired working memory. In response to restraint AS, instant stress reactivity including locomotor behavior and corticosterone induction was impaired in Srf mutant mice. Interestingly, even several weeks after previous AS exposure, SRF-deficient mice showed long-lasting AS-associated changes including altered locomotion, metabolism, energy expenditure, and cardiovascular changes. This suggests a requirement of SRF for mediating long-term stress coping mechanisms in wild-type mice. SRF ablation decreased AS-mediated IEG induction and activity of the actin severing protein cofilin. In summary, our data suggest an SRF function in immediate AS reactions and long-term post-stress-associated coping mechanisms.
Published online: 2 December 2016
Gesehen am 21.08.2018